Citron—Citrullus lanatus (Thunb.) Mansf. var. citroides (Bailey) Mansf. - James M. Stephens (EDIS, 2003)
This document describes the citron melon (Citrullus lanatus var. citroides), a fruit closely related to watermelon but inedible when raw. Often called stock or preserving melon, it is distinct from the citrus citron. The fruit is small, tough, and white-fleshed, commonly used for preserves and pickles. It grows similarly to watermelon, requiring bee pollination, and is often found in old fields and roadsides in Florida. Cross-pollination with watermelon is common but not problematic unless seeds are saved for planting. Original publication date May 1994.